Housing and Social and Material Vulnerabilities. Issue 4 (1st October 2016) - Bartram, Robin
Abstract: Issues around the materiality of housing and inequality are increasingly important today. Yet, housing researchers have not settled on conceptual tools to account for and study the role of both social and material characteristics of people and their housing. Outlining a new research agenda, I use the idea of social and material vulnerabilities to stress the need to always account for how material and social characteristics relate in myriad ways that render some people and certain material environments more vulnerable than others. I suggest typologies and comparisons as useful tools researchers might use to investigate relationships – that can be malleable yet are often institutionalized – between social and material vulnerabilities, and caution against some assumptions that may skew our understandings of housing. I argue that attending to the social and material vulnerabilities of housing reveals ways in which the materiality of other built environments might also be important.